Exploration of Financial Statements CV. Wian Mandiri Based on Financial Accounting Standards for Micro, Small, and Medium Entities - Dimas Wahyu Darmawan; Nina Martiana; Diyah Probowulan (West Science Business and Management, 2024)
The title of the research is "Exploration of CV. Wian Mandiri Financial Report Based on the Standard of Financial Accounting for Micro, Small, and Medium-Sized Entities." The research uses a qualitative descriptive method with a case study approach on CV. Wian Mandiri. Data was collected from observation, interviews, and documentation, and then analyzed using a descriptive method. The research aims to determine the practice of recording and preparing financial reports based on SAK EMKM in CV. Wian Mandiri, located at Bhineka 1 Street, Number 52, Pasir Gunung Selatan, Cimanggis Depok, West Jakarta. The results of the research show that CV. Wian Mandiri's financial report is still simple, recording only income and expenses, which are then accumulated to determine the profit and loss at the end of the month. After applying SAK EMKM in reconstructing the financial report, it was found that CV. Wian Mandiri's profit and loss report showed a profit of Rp. 30,042,000.00 in October and Rp. 29,887,000.00 in November. The balance sheet report for October and November showed total assets of Rp. 76,408,000.00 and Rp. 106,446,000.00, with equity and liabilities of Rp. 76,408,000.00 and Rp. 106,446,000.00, respectively. The notes to the financial report, which describe the general statements of the entity, the accounting policies adopted, and explanations about the accounts on the income report, cannot be explained because the company considers them to be within the company's private domain.